Heavily Indebted Poor Countries Initiative : List of Ring-Fenced Countries that Meet the Income and Indebtedness Criteria at end-2004. (Policy Papers; Policy Paper, 2006)
This paper identifies the countries that meet the enhanced Heavily Indebted Poor Countries (HIPC) Initiative's income and indebtedness eligibility criteria based on end-2004 data. It also updates the status of these countries toward qualifying for debt relief and presents cost estimates of debt relief.